Type-2 Neutrosophic Numbers for Impact Evaluation of Sports on the Psychological and Emotional Regulation of Rural Children - Ming Yuan; Jing Huang; Xinhuan Duan; Xin Hu (Neutrosophic Sets and Systems)
The role of sports in the psychological and emotional development of children has gained increasing attention, particularly in rural areas where social and educational opportunities may be limited. This study examines the impact of structured and unstructured sports activities on the emotional regulation, cognitive development, and overall well-being of rural children. By analyzing key psychological factors such as self-confidence, stress reduction, and social interaction, the research highlights how engagement in sports contributes to emotional stability and mental resilience. The study employs a comprehensive evaluation framework based on multi-criteria decision-making (MCDM) methods to assess the effectiveness of different sports programs. Two MCDM methods are used, such as LBWA method to compute the criteria weights and the TOPSIS method to rank the alternatives. These methods are used under the Type-2 Neutrosophic Set to deal with uncertainty information. Application is employed to show the validation of the proposed approach. Alos, comparative analysis is conducted. This study provides valuable guidance for policymakers, educators, and community leaders in designing sports initiatives that effectively support the psychological well-being of rural children.